2002
DOI: 10.1038/sj.bdj.4801338a
|View full text |Cite
|
Sign up to set email alerts
|

The fate of the carious primary teeth of children who regularly attend the general dental service

Abstract: Treatment by extraction was common, but GDPs restored the majority of carious primary molar teeth of their regularly attending child patients. The bulk of carious teeth exfoliated naturally irrespective of whether they were filled or not. The reasons for these findings require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 0 publications
5
43
0
Order By: Relevance
“…Traditional restorative technique or restoring a decayed tooth with a crown (stainless steel crown/composite strip crown) was the most preferred restoration method among PDs, whereas atraumatic restorative technique was more popular among GDPs. This is concurrent with other studies that also demonstrated that GDPs were less interventionist in the dental care for children. The treatments that GDPs opted for were simpler in nature and mostly temporary measures to solve the problem.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Traditional restorative technique or restoring a decayed tooth with a crown (stainless steel crown/composite strip crown) was the most preferred restoration method among PDs, whereas atraumatic restorative technique was more popular among GDPs. This is concurrent with other studies that also demonstrated that GDPs were less interventionist in the dental care for children. The treatments that GDPs opted for were simpler in nature and mostly temporary measures to solve the problem.…”
Section: Discussionsupporting
confidence: 79%
“…Although comprehensive restorative approach to the management of children with carious primary teeth is advocated, GDPs tended to treat caries conservatively. The dental practitioners' clinical decision making and the actual way in which dental care and treatment is provided to children merit attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the training of new members of any specialist workforce should always be underpinned by research evidence as change and adaptation are part of the working lives of all professionals. Recent evidence from the UK 1–3 raises questions on the appropriateness and clinical value of restoring the primary dentition. These studies were retrospective in nature, but they suggest that paediatric dental specialists need to be more reflective and investigate further the appropriateness of the treatment regimes currently offered to young children for the primary dentition.…”
mentioning
confidence: 99%
“…A decade ago, two retrospective studies reported the fate of cavitated carious primary teeth until exfoliation. They revealed that 82% of such teeth exfoliated without symptoms . This finding is supported by a recently published prospective study into the natural course of cavitated primary teeth among on average 8‐year‐olds .…”
mentioning
confidence: 55%
“…The dependent variable was the survival rate of primary molars until exfoliation that had been treated according to the three treatment protocols (CRT, ART, and UCT). The independent variables were age at baseline (6–7 years), gender, mean dmft score at baseline, type of surface (single, multiple), operator , and type of molar (1st, 2nd). A treated tooth was extracted because of toothache, dental sepsis (fistula/abscess), or pulp exposure.…”
Section: Methodsmentioning
confidence: 99%